ОБМЕЖЕННЯ ПРИНЦИПУ СВОБОДИ ДОГОВОРУ У СФЕРІ НАДАННЯ БАНКІВСЬКИХ ПОСЛУГ - Ustymenko, A.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2020)
Today, the consumer of banking services is actually a weak party, being in a wide range of financial (banking) relations. Due to the different status of the parties, one being able to dictate their conditions in the legal relationship and the other having no real influence on the counterparty. One of the legal guarantees is the extension of the scope of contractual freedom also to bank deposit relations, account opening and servicing, credit relations, etc. Accordingly, the limitation inherent in the very nature of contractual freedom is an integral part of it. In this connection, the role of contractual freedom in the private and public legal sphere, which is characterized by the existence of State coercion, is of particular interest. The banking sector of the economy proves the existence of contractual freedom in organic unity with its limitations. A practical problem is the effect on the contractual freedom of public authority or a body authorized to administer justice. This creates an imbalance of interest in favor of public law against private law. The purpose of the article is to study the impact, place and role of the principle of freedom of contract at the stages of conclusion, modification and termination of contracts in the branch of banking services. The article examines the relations of the bank and its clients within the framework of such contractual types (types) which are distinguished by publicity in the sense of article 633 of the Ukrainian Civil Code: bank account contract, bank deposit contract. The author’s vision of the principle of freedom of contract through the dialectic of unity of contract freedom and its limitations is presented and justified. This approach is the basis for the study of bank-client relations. The conditions for limiting the principle of freedom of contract beyond the elements of the traditional triad in the banking sphere at the stages of conclusion, performance, modification and termination are also described. The article affirms the existence of limitations to the principle of freedom of contract not only by law but also by the principles of law (general and special), by contract, by the customs of business and by the activities of the State in the form of administrative and judicial measures. REFERENCES 1. Berveno S.M. Problemy dohovirnoho prava Ukrainy: monohrafiia. Kyiv: Yurinkom Inter, 2006. 392 p. [in Ukrainian].2. Horiev V.O. Svoboda dohovoru yak zahalna zasada tsyvilnoho zakonodavstva Ukrainy: dys. … kand. yuryd. nauk: 12.00.03. Kharkiv, 2007. 203 p. [in Ukrainian].3. Luts A.V. Svoboda dohovoru v tsyvilnomu pravi Ukrainy: dys. … kand. yuryd. nauk: 12.00.03. Lviv, 2001. 166 p. [in Ukrainian].4. Oliukha V.H. Tsyvilno-pravovyi dohovir: poniattia, funktsii ta systema: dys. … kand. yuryd.nauk: 12.00.03. Kyiv, 2003. 175 p. [in Ukrainian].5. Merezhko A.A. Dogovor v chastnom prave. Kiev: Justinian, 2003. 176 p. [in Russian].6. Jagofarova I.D. Pravo kak mera ogranichenija svobody: dis. … kand. jurid. nauk : 12.00.01. Ekaterinburg, 2004. 206 p. [in Russian].7. Nersesjanc V.S. Pravo — matematika svobody. Opyt proshlogo i perspektivy. Moscow,1996. 157 p. [in Russian].8. David P. Weber. Restricting the Freedom of Contract: A Fundamental Prohibition. Yale Human Rights and Development Journal. 2013. Vol. 16. Iss. 1. P. 51-103. URL: https://digitalcommons.law.yale.edu/yhrdlj/vol16/iss1/2/9. Rishennia Konstytutsiinoho Sudu Ukrainy vid 10.11.2011 No. 15-rp/2011 (sprava No. 1-26/2011). URL: https:// zakon.rada.gov.ua/laws/show/v015p710-11#Text [in Ukrainian].10. Tsiukalo Yu.V. Shchodo rozuminnia svobody dohovoru: teoretyko-prykladnyi aspekt. Chasopys Kyivskoho universytetu prava. 2013. No. 1. P. 209-212 [in Ukrainian].11. Harahonych O.V. Hospodarska pravosubiektnist aktsionernykh tovarystv: avtoref. dys. … dokt. yuryd. nauk: 12.00.04. Kyiv, 2020. 34 p. [in Ukrainian].12. Rishennia Hospodarskoho sudu mista Kyieva vid 01.03.2018 u spravi No. 910/22248/17. URL: http://reyestr.court.gov.ua/Review/72543536 [in Ukrainian].13. Postanova Velykoi Palaty Verkhovnoho Sudu vid 05.05.2020 u spravi No. 750/3917/17. URL: http://reyestr.court.gov.ua/Review/89822237 [in Ukrainian].14. Okrema dumka suddi Velykoi Palaty Verkhovnoho Sudu O.M. Sytnik vid 05.05.2020 u spravi No. 750/3917/17. URL: http://reyestr.court.gov.ua/Review/89793583 [in Ukrainian].15. Postanova Kasatsiinoho Hospodarskoho Sudu u skladi Verkhovnoho Sudu vid 25.04.2019 u spravi No. 910/1555/18. URL: http://reyestr.court.gov.ua/Review/81435365 [in Ukrainian].16. Postanova Velykoi Palaty Verkhovnoho Sudu vid 30.10.2018 u spravi No. 914/3217/16. URL: http://reyestr.court.gov.ua/Review/78112035 [in Ukrainian].17. Postanova Verkhovoho Sudu Ukrainy vid 09.04.2014 u spravi No. 6-12tss14. URL: http://reyestr.court.gov.ua/Review/38376811 [in Ukrainian].